Anesthesia Alert—A Preoperative Safety Concept for the Surgeon - Protyniak, Bogdan; Pearce, Paul; Giambarberi, Luciana; Kumar, Atul; Goldfarb, Michael A. (Scientific Research, 2015)
Background: Advances in modern medicine and surgical technique have allowed patients with multiple comorbidities to undergo invasive surgery electively. This places additional stress on hospital resources to anticipate and deal with potential complications. We have introduced a preoperative safety concept called “Anesthesia Alert”. The surgeon or preoperative interviewing anesthesiologist assigns an Anesthesia Alert when booking to denote possible difficulty with anesthesia induction or intubation. As a result, two anesthesiologists and fiber optic equipment are made available on the day of surgery. Methods: A retrospective study of patients from all surgical specialties who were assigned Anesthesia Alerts between January 2012 and November 2012. Records were analyzed for reasons requiring Anesthesia Alerts. Patient demographics, comorbidities, and perioperative complications were reviewed. Results: A total of 112 patients formed this study group. Difficult airway comprised the majority of Anesthesia Alerts (n = 75, 67.0%). Hypertension was the most prevalent comorbidity among patients. There were only 7 patients (6.3%) admitted to the ICU postoperatively and no mortalities. Conclusion: Perioperative patient safety is an evolving concept that requires a team approach amongst the surgeon, anesthesiologist, and operating room staff. An Anesthesia Alert raises awareness for possible complications during anesthesia induction as well as allocates resources to increase patient safety and avoid preoperative delays. Most importantly, this concept places the onus on the surgeon to alert the anesthesiologist for possible complications during induction and extubation.
Keywords: Difficult Airway; Anesthesia Complications; Operating Room Safety